2012
DOI: 10.1002/psc.2467
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative folding and preparation of α‐conotoxins for use in high‐throughput structure–activity relationship studies

Abstract: α-Conotoxins are peptide neurotoxins that selectively inhibit various subtypes of nicotinic acetylcholine receptors. They are important research tools for studying numerous pharmacological disorders, with profound potential for developing drug leads for treating pain, tobacco addiction, and other conditions. They are characterized by the presence of two disulfide bonds connected in a globular arrangement, which stabilizes a bioactive helical conformation. Despite extensive structure-activity relationship studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 56 publications
2
29
2
Order By: Relevance
“…We also tested the effect of co-solvents, IPA and DMSO, on folding reactions. We observed that, in contrast to other studies [22], IPA addition significantly decreased the yield of globular isomer (runs 41–48). IPA addition improved the yield of ribbon isomer yield, suggesting that IPA is a key factor for oxidative folding of the ribbon isomer.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…We also tested the effect of co-solvents, IPA and DMSO, on folding reactions. We observed that, in contrast to other studies [22], IPA addition significantly decreased the yield of globular isomer (runs 41–48). IPA addition improved the yield of ribbon isomer yield, suggesting that IPA is a key factor for oxidative folding of the ribbon isomer.…”
Section: Resultscontrasting
confidence: 99%
“…As observed by other researchers for α-conotoxin folding, temperature is not a significant factor for globular isomer yield, while the pH plays a key role [22]. Overall, our results of temperature and pH experiments are consistent with prior studies for α-conotoxins.…”
Section: Resultssupporting
confidence: 92%
“…28 The formation of disulfide bonds was achieved by cosolvent assisted oxidative folding (50% isopropanol in aqueous ammonium bicarbonate buffer at pH 8.2), which was previously shown to maximize the accumulation of the native globular isomer of α-conotoxin BuIA. 29 A simplified desalting procedure that employed disposable solid-phase extraction (SPE) columns was used for the rapid and efficient preparation of library samples in parallel prior to initial pharmacological screening. 29 Note that the globular and ribbon isomers of selected second generation individual analogues were later synthesized separately to confirm their identity and were purified by RP-HPLC prior to formal functional characterization.…”
Section: Resultsmentioning
confidence: 99%
“…29 A simplified desalting procedure that employed disposable solid-phase extraction (SPE) columns was used for the rapid and efficient preparation of library samples in parallel prior to initial pharmacological screening. 29 Note that the globular and ribbon isomers of selected second generation individual analogues were later synthesized separately to confirm their identity and were purified by RP-HPLC prior to formal functional characterization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation